2015
DOI: 10.1519/jsc.0000000000000958
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low- vs. High-Load Resistance Training on Muscle Strength and Hypertrophy in Well-Trained Men

Abstract: The purpose of this study was to compare the effect of low- versus high-load resistance training (RT) on muscular adaptations in well-trained subjects. Eighteen young men experienced in RT were matched according to baseline strength and then randomly assigned to 1 of 2 experimental groups: a low-load RT routine (LL) where 25-35 repetitions were performed per set per exercise (n = 9) or a high-load RT routine (HL) where 8-12 repetitions were performed per set per exercise (n = 9). During each session, subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
305
0
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 328 publications
(347 citation statements)
references
References 55 publications
23
305
0
19
Order By: Relevance
“…In studies of adult populations where effort is controlled between different loading conditions by having participants train to momentary concentric failure LL conditions consistently produce higher volume-load performances compared with HLs (Barcelos et al, 2015;Mitchell et al, 2012;Schoenfeld et al, 2015;. In addition, where relative loadings are kept constant absolute volume-load typically increases over the course of a RT intervention due to participants' increases in strength (Ribeiro et al, 2015).…”
Section: P a G Ementioning
confidence: 99%
See 2 more Smart Citations
“…In studies of adult populations where effort is controlled between different loading conditions by having participants train to momentary concentric failure LL conditions consistently produce higher volume-load performances compared with HLs (Barcelos et al, 2015;Mitchell et al, 2012;Schoenfeld et al, 2015;. In addition, where relative loadings are kept constant absolute volume-load typically increases over the course of a RT intervention due to participants' increases in strength (Ribeiro et al, 2015).…”
Section: P a G Ementioning
confidence: 99%
“…However, the absolute difference between the groups was very small and so it is likely that any difference is relatively meaningless. Further, most research to date suggests that when RT is performed to momentary failure adaptations such as strength and absolute endurance are likely to be similar (Barcelos et al, 2015;Mitchell et al, 2012;Schoenfeld et al, 2015;. Most research to date however has seemingly been conducted with adult populations, including the elderly.…”
Section: P a G Ementioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that strength and hypertrophy can be optimized via complete motor unit activation using heavy loads. However, a recent study has suggested that low-intensity exercise such as 30-40% 1RM can induce a similar level of muscle hypertrophy as highintensity resistance training [12][13][14]. Mitchell et al [12] have demonstrated an effect of resistance training with low loads (30% 1RM) and high repetitions on muscle hypertrophy.…”
Section: Training Protocols For Muscle Hypertrophy and Vo2max Improvementioning
confidence: 99%
“…However, improvement in the one set and 3 sets groups at 80% 1RM was higher than that in the 3 sets at 30% 1RM group after training. Schoenfeld et al [13] have examined the effect of low-load and high-load training on muscle strength and hypertrophy in well-trained men. They divided subjects into two groups: a low-load training group (n = 9) and a high-load training group (n = 9).…”
Section: Training Protocols For Muscle Hypertrophy and Vo2max Improvementioning
confidence: 99%